Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Divide using synthetic division (x^3 - 4x + 6) ÷ (x+3) =

Sagot :

Answer:

Quotient = x² - 3x + 5

Remainder = 9

Explanation:

To make the synthetic division, we need to rewrite the dividend with all the degrees of the exponents, so:

x³ - 4x + 6 = x³ + 0x² - 4x + 6

Then, we will use the coefficient of each term: 1, 0, -4 and 6

On the other hand, the divisor should have the form (x - a), so:

x + 3 = x - (-3)

Therefore, a = -3, and we will use this number for the synthetic division.

Finally, the synthetic division is:

Where the first number goes down, then the blue -3 is calculated as the number as 1 x -3, and the yellow -3 is equal to the sum of the number numbers 0 and -3, so: 0 + (-3) = -3

In the same way, 9 = -3 x -3 and 5 = -4 + 9

Finally, -15 = 5 x -3 and -9 = 6 - 15

Now, the coefficients 1, -3, and 5 give us the quotient of the division, and -9 is the remainder. So, the solution of the division is:

[tex]\begin{gathered} quotient=x^2-3x+5 \\ \text{remainder}=-9 \end{gathered}[/tex]

View image VilmaD609234
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.